Fracture Toughness and Hardness studying for Polymer-Ceramic Composite - Baghdad Science Journal (مجلة بغداد للعلوم)
A particulate composite material was prepared by adding the Titanium dioxide (TiO2) with a particle size of (75-150) µm to Epoxy resin at weight percentage of (10%,20%,30%,40%,50%).The following some mechanical properties were studied,fracture toughness, hardness.casting preparation methods were used in this study includes preparing plate of matrix and composites. specimens were prepared according to ASTM for the Mechanical properties tests. After that Another samples were heat treated for three and six hour at 65C?. Fracture toughness (Kic) represent for stress intensity factor results were showed that the curve of three hours aging increases in fracture toughness (Kic) for composites but for six hours aging increases fracture toughness (Kic) for polymer matrix. Hardness tests was showed that hardness results increased with the increase in weight fraction while a samples that not treated thermally have higher hardness than the samples for treated thermally. Finally, fracture surfaces were showed morphology failure surfaces by using an optical Microscope.